PENGARUH MEDIA SOSIAL “FACEBOOK” TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MA BAHRUL ULUM DESA AIR EMAS KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Lutfia Marfiani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Facebook is a social media (social network) that can be used by users to get to know and communicate with each other in a variety of purposes and also be recreational. Facebook can provide benefits for its users to be able to communicate with friends and facilitate the distribution of information. But the reality at this time is that Facebook gives a lot of negative things to students. This is evidenced that many students more often open facebook than textbooks, so that children's learning outcomes have decreased in the subjects of the Morals. Based on these problems the researchers wanted to find out how the influence of social media facebook on student learning outcomes. The purpose of this study was to determine the effect of Facebook social media on student learning outcomes in moral subjects and factors that influence Facebook social media on student learning outcomes in moral subjects in MA Bahrul Ulum Singingi. The data analysis technique that researchers use is to use a quantitative approach, with the type of simple linear regression research with the help of the Statistics Program for Socoal Science (SPSS) 20.0 Windows. And using data collection techniques observation, interviews, questionnaires and documentation. The results of the study, find out the coefficient of determination (R squere) of 0.017 (is the square of the correlation coefficient, or 0.132 x 0.132 = 0.017). The magnitude of the coefficient of determination (R square) 0.017 equals 1.7%, the figure implies that social media Facebook has no effect on student learning outcomes in moral subjects by 1.7%. While the rest is influenced by other variables. Keyword: "Facebok" Media Social, The Eye Of Akhlak Achievement